DNA vaccines against tuberculosis. (December 2014) - Bruffaerts, Nicolas; Huygen, Kris; Romano, Marta
Abstract : Introduction: Tuberculosis (TB) remains a major health problem and novel vaccination regimens are urgently needed. Areas covered: DNA vaccines against TB have been tested in various preclinical models and strategies have been developed to increase their immunogenicity in large animal species. DNA vaccines are able to induce a wide variety of immune responses, including CD8 + T-cell-mediated cytolytic and IFN-γ responses. DNA vaccination may be valuable in heterologous prime-boost strategies with the currently used bacillus Calmette–Guérin (BCG) vaccine. This approach could broaden the antigenic repertoire of BCG and enhance its weak induction of MHC class I-restricted immune responses. Expert opinion: DNA vaccines offer a number of advantages over certain other types of vaccines, such as the induction of robust MHC class I-restricted cytotoxic T lymphocyte (CTL), their generic manufacturing platform and their relatively low manufacturing costs. Because of their strong potential for inducing memory responses, DNA vaccines are particularly suited for priming immune responses. Furthermore, DNA vaccine technology may help antigen discovery by facilitating screening of candidate vaccines. Co-administration of BCG with plasmid DNA coding for immunodominant, subdominant and phase-specific antigens, poorly expressed by BCG, may lead to the development of improved TB vaccines.